2009
DOI: 10.1007/s00248-009-9551-7
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Multidrug-Resistant Pseudomonas aeruginosa on Hydrocarbon-Contaminated Sites

Abstract: The main aim of this paper was the comprehensive estimation of the occurrence rate and the antibiotic-resistance conditions of opportunistic pathogen Pseudomonas aeruginosa in hydrocarbon-contaminated environments. From 2002 to 2007, 26 hydrocarbon-contaminated sites of Hungary were screened for the detection of environmental isolates. Altogether, 156 samples were collected and examined for the determination of appearance, representative cell counts, and antibiotic-resistance features of P. aeruginosa. The det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…The analysis of samples collected at the spring of this river contained almost no P. aeruginosa whereas samples located downstream in areas exposed to run‐off from highways or agricultural lands showed an increased P. aeruginosa density. Similarly, a recent screening for the occurrence rate of P. aeruginosa in hydrocarbon‐contaminated sites of Hungary showed that the presence of this species was in connection with human activities (Kaszab et al. , 2009).…”
Section: Discussionmentioning
confidence: 98%
“…The analysis of samples collected at the spring of this river contained almost no P. aeruginosa whereas samples located downstream in areas exposed to run‐off from highways or agricultural lands showed an increased P. aeruginosa density. Similarly, a recent screening for the occurrence rate of P. aeruginosa in hydrocarbon‐contaminated sites of Hungary showed that the presence of this species was in connection with human activities (Kaszab et al. , 2009).…”
Section: Discussionmentioning
confidence: 98%
“…An intriguing observation is the frequent isolation of P. aeruginosa from hydrocarbon contaminated sites both aquatic (Bartha, 1977; Bhattacharya et al, 2000) and terrestrial (Norman et al, 2002; Kaszab et al, 2010) hydrocarbon-impacted environments. Despite the low number of samples tested our detection was very successful since P. aeruginosa was detected in 4 out of the 5 samples.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Green et al (1974) recovered it from Californian soils and concluded about agricultural soil as a natural habitat for the bacterium since the soils sampled had no known organic fertilizer or animal pasturing background, and irrigation water was free of the bacterium. Further studies showed that P. aeruginosa is often present within polluted soils from various geographical regions and participates to the degradation of the hydrocarbons (Garcia-Junco et al, 2001; Norman et al, 2002; Kaszab et al, 2010). To our knowledge, no recent studies have been performed to better appreciate its relative abundance within the global soil bacterial communities, and to assess the influence of soil characteristics and anthropogenic constraints on its distribution.…”
Section: Introductionmentioning
confidence: 99%
“…17 However, many studies use Pseudomonas strains isolated from contaminated soil and water, [18][19][20][21] and in the case of living cells, the risk of multiplication of multi-resistant cultures is high. 22,23 In this study, the biosorption characteristics of lyophilized P. aeruginosa PAO1 laboratorial bacterial strain for cadmium(II) and lead(II) ions in aqueous suspension is presented. The effect of pH, contact time and initial heavy metal concentrations on the biosorption were investigated for both cations.…”
Section: Introductionmentioning
confidence: 99%